Ultra-high pressure-assisted preparation of cowhide gelatin as a promising fat substitute: Improve the nutrition ratio and antioxidant capacity of beef patties. (July 2022) - Gao, Yanlei; Qiu, Yi; Nan, Huanli; Wang, Liyuan; Yang, Dawei; Zhang, Li; Yu, Qunli
Graphical abstract: Highlights: UHP-assisted preparation of cowhide gelatin was used as fat replacer for beef patty. Use of cowhide gelatin for beef patties with lower cooking loss/higher moisture. Beef fat replacement with gelatin reduced saturated fat level from 42.1% to 56.6%. Higher antioxidant capacity in patties showed by substituting gelatin as beef fat. The gelatin content and the antioxidant capacity of patty were highly correlated. Abstract: In this study, low-fat beef patties were prepared by replacing different proportions of beef fat (0, 25, 50, 75, and 100%) with ultra-high pressure–assisted cowhide gelatin. The quality characteristics, lipid oxidation, protein oxidation, and fatty acid profile of beef patties during cold storage at 4 ℃ (0, 7, 14, 21, and 28 days) were evaluated. The results showed that the addition of cowhide gelatin increased the protein content and reduced the fat content of beef patties. The saturated fatty acid (SFA) content of beef patties significantly reduced and the polyunsaturated fatty acid (PUFA) content significantly increased with the increase in the replacement ratio. Especially, the 100% substitution group had the highest PUFA content; the SFA content and the n -6/ n -3 ratio could be reduced by about 56% and 31%, respectively. During the cold storage period, the moisture content of beef patties increased significantly, while the cooking loss was the opposite, with the increase in the fat replacement rate. The L * and a * values of raw patties prepared with gelatin were significantly higher than those in the control group. Furthermore, adding cowhide gelatin significantly reduced the thiobarbituric acid, peroxide, and carbonyl contents of patties, but increased their total sulfhydryl content throughout the refrigeration period. Thus, it was concluded that cowhide-based gelatin was a promising alternative to replace beef fat in low-fat beef patties.